Experimental study of a high power free electron maser based on a co-axial two-dimensional Bragg cavity - Whyte, C; Ronald, K; Phelps, A; Konoplev, I; McGrane, P; Cross, A; He, W; Robertson, C; Ginzburg, N; Peskov, N; Sergeev, A; Thumm, M (2004)
The generation of high power microwave radiation from a two-dimensional (2D) Bragg coaxial Free Electron Maser (FEM) is reported. Two 2D Bragg structures positioned at the input and output of an oversized co-axial interaction region were used to define the cavity of the FEM. Measurements of the transmission coefficient of the 2D Bragg structures were conducted and experimental results compared with theoretical predictions. A 1 kA, 475 kV annular electron beam of diameter 7 cm was used to generate microwave radiation, the frequency of this radiation lay within the reflection zone of the 2D Bragg cavity. © 2004 D.V. Efremov Scientific Research Institute of Electrophysical Apparatus.